A predictive model for disease progression in non-severely ill patients with coronavirus disease 2019. Issue 1 (16th July 2020) - Ji, Mengyao; Yuan, Lei; Shen, Wei; Lv, Junwei; Li, Yong; Chen, Jia; Zhu, Chaonan; Liu, Bo; Liang, Zhenzhen; Lin, Qiang; Xie, Wenjie; Li, Ming; et al.
Over the past 3 months, coronavirus disease 2019 (COVID-19) has emerged across China and developed into a worldwide outbreak [1]. The disease has caused varying degrees of illness. The proportion of patients with COVID-19 with non-severe illness was 84.3% on admission, and severe cases accounted for 15.7% [2]. Most of the non-severe pneumonia patients would gradually alleviate and be cured with treatment, while others would rapidly progress to severe illness, which has a poor prognosis [3, 4]. As recently reported, the cumulative risk of the composite end-point was 3.6% in all COVID-19 patients, and the cumulative risk was 20.6% for severe illness [2]. A predictive model for COVID-19 https://bit.ly/2WHiEkJ